High price : a neuroscientist's journey of self-discovery that challenges everything you know about drugs and society - Hart, Carl L. (Harper, 2013)
As a youth, Carl Hart didn't realize the value of school; he studied just enough to stay on the basketball team. At the same time, he was immersed in street life. Today he is a cutting-edge neuroscientist--Columbia University's first tenured African American professor in the sciences--whose landmark, controversial research is redefining our understanding of addiction. In this provocative memoir. he recalls his journey of self-discovery. He examines the relationship among drugs, pleasure, choice, and motivation, both in the brain and in society. His findings shed new light on common ideas about race, poverty, and drugs, and explain why current policies are failing. Determined to make a difference, he tirelessly applies his scientific research to help save real lives. But balancing his former street life with his achievements today has not been easy--a struggle he reflects on publicly for the first time. This powerful story of hope will alter the way we think about how we can effect change.--From publisher description.